A photo-assisted electrocatalyst coupled with superoxide suppression for high performance Li-O2 batteries. (July 2021) - Li, Dewang; Lang, Xiuyao; Guo, Yong; Wang, Yiqiao; Wang, Yanyin; Shi, Hucheng; Wu, Shichao; Wang, Weichao; Yang, Quan-Hong
Abstract: Li-O2 batteries are one of the most promising next generation batteries due to their high energy density. However, they suffer from high charge overpotentials and severe side reactions. Here we report a bifunctional CeVO4 catalyst that not only lowers the charge potential by a photo-assisted mechanism, more importantly, promotes the efficient conversion of highly reactive oxidative intermediates to Li2 O2, thus avoiding the oxidative decomposition of the electrolyte/cathode during discharge. Benefiting from its efficient electrocatalysis and the improved charging ability, 1.6x higher discharge capacity up to 6.14 mAh cm -2, low charge potential of 3.48 V and stable cycling performance are simultaneously achieved. Theoretical calculation and in-situ Raman spectra confirm the superior adsorptive and conversion ability of superoxide species by electrochemical reduction and chemical disproportionation reactions on the CeVO4 catalyst. These results indicate an effective strategy to break through the reported limitations of photo-assisted cathodes that are of a low electrocatalysis ability and limited discharge capacity. The significance of retaining a high energy density in photo-assisted Li-O2 batteries is highlighted. Graphical abstract: CeVO4 as a bifunctional catalyst in Li-O2 battery cathode achieves superior electrocatalytic effect of fast conversion of superoxides to Li2 O2 during discharge, and photo-assisted catalytic effect endowing reduced charge overpotential under illumination. Both of the effects contribute to the suppression of side products, thus pushing the capacity outputs and cycling stability. ga1 Highlights: CeVO4 serves as an unique bifunctional catalyst, facilitating conversion of superoxide intermediates during discharge and achieving charge overpotential reduction under photo-assisted condition. Theoretical calculation and in-situ Raman spectra confirm the improved kinetics of oxygen reduction reaction on the surface CeVO4 catalyst and the large suppression of side reactions. The photo-assisted Li-O2 batteries with CeVO4 catalysts realize the discharge capacity increase by 1.6 times and high cycling stability at large current densities.